Organizational wrongdoing: A theoretical essay on the malleability of the course of action of ethical decisions - Rocha, Fabíola Caldeira de Medeiros; Roglio, Karina de Deá (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
In this theoretical essay, we present a reflection on organizational irregularities (wrongdoing), considering ethics and morality from a sociological perspective, and exploring the rules used to guide human behavior in organizational decision-making. To this end, we reviewed the dominant and emerging sociological perspectives for organizational wrongdoing; behavioral ethics; and the rationalization of unethical behavior in organizations. In this reflection, we move away from the implicit thought that the organization's participants are regulated only by external control agents and from the dichotomous view of ethical decisions and call the attention for a third alternative: that of socially justified choices, which are a new possibility of analyzing wrongdoing, still poorly understood and with implications for organizational theory.